Reducing healthcare associated infections by adopting a proactive, preventive approach - Whatley, Vanessa (International Journal of Infection Control, 2007)
An increase in Clostridium difficile associated diarrhoea, rapidly rising MRSA bacteraemias and new cases of healthcare associated MRSA colonisation prompted the Royal Wolverhampton Hospitals NHS Trust to review and reform their infection control priorities. The aim was to reduce healthcare associated infections and reach the Department of Health MRSA bacteraemia target for the Trust. By changing the emphasis from a reactive ‘infection control’ approach to a more proactive ‘infection prevention’ outlook; improving ward to board accountability; and implementing a number of infection prevention initiatives, the number of cases of hospital acquired infections due to Clostridium difficile, MRSA and Acinetobacter baumannii within the Trust have been effectively reduced.